Conflicting Claims behind a Consensus: A Critical Analysis of the Effect of Implicit Polyphony on the Argumentative Orientation in Science-Policy Discourse on Climate Change - Kanerva, Julia (My University, 2017)
This MA Thesis aims to critically investigate the role of discourse for the issue of climate change. It focuses on the discourse produced at science-policy interface by one of the most authoritative actors in the climate change debate, the Inter-governmental Panel on Climate Change (IPCC). The present study adopts a critical discourse-analytic approach and a linguistic method to assess the Summary for Policymakers (SPM) produced as a part of the IPCC’s Fifth Assessment Report. The research is motivated by previous studies demonstrating the challenging nature of communicating on climate change. Furthermore, the study is dedicated to finding explanations for controversy and inaction that continue to characterise society’s responses to the scientific information on climate change. The IPCC is widely considered as an objective scientific organisation. The present study aims to assess its objectivity by uncovering implicit argumentation in the SPM and analysing the argumentative orientation in relation to whether it is directed towards encouragement or discouragement for climate action. Implicit argumentation is uncovered with a method based on the framework of Scandinavian Theory of Linguistic Polyphony. The polyphonic constructions are identified by detecting polyphonic markers but in the text. The 23 constructions of implicit polyphony found in the data were concerned with three broad themes: urgency, ability to respond, and adverse effects of mitigation. Seven constructions oriented the discourse towards encouragement for action by highlighting the urgency of climate change or positively evaluating the ability to respond. In contrast, the majority of the constructions oriented the discourse towards discouragement. These constructions were undermining statements of urgency and positive evaluations of the methods available by highlighting the following aspects: 1) uncertainties in the current knowledge relating to the urgency of climate change, 2) negative evaluations of the potential of current knowledge to inform mitigation and adaptation, and 3) negative consequences of mitigation. The findings were discussed according to the traditions of critical discourse analysis from the point of view of the production as well as the consumption of the text. The pursuit of consensus, disciplinary bias, political pressures, and influence of the neoliberal ideology were among the explanations given to the dominance of discouragement in the polyphonic constructions in the SPM. Regarding the reception of the report, the dominance of discouragement was argued to offer discursive tools for policymakers to avoid responsibility and delay climate action. Furthermore, this argumentative orientation was suggested to further legitimate the dominant economic paradigm. It was concluded that transparency concerning the bias and increased disciplinary balance may help to tackle the discouraging effect of the reports in the future.